Evaluation of a novel lentiviral vaccine expressing KMP11‐HASPB fusion protein against Leishmania infantum in BALB/c mice. (6th October 2016) - Mortazavidehkordi, N.; Farjadfar, A.; Khanahmad, H.; Ghayour Najafabadi, Z.; Hashemi, N.; Fallah, A.; Najafi, A.; Kia, V.; Hejazi, S. H.
Summary: Hydrophilic acylated surface protein B (HASPB) is an immunogenic Leishmania protein against which antibodies are produced in the sera of cutaneous and visceral Leishmaniasis (VL) patients. Kinetoplastid membrane protein 11 (KMP11) is another protein antigen of Leishmania which is reported as a promising candidate for vaccination of VL. It is a highly conserved surface protein present in all members of kinetoplastid family and is expressed in both promastigotes and amastigotes. In this study, the coding sequence of KMP11 and HASPB was cloned into a pCDH‐cGFP lentiviral vector as a fusion protein. The gene expression was confirmed using RT‐PCR and Western blot methods. After injection of the recombinant KMP11‐HASPB‐expressing lentiviruses to BALB/c mice, using ELISA technique, a significant increase in IFN‐γ and IL‐4 as well as IgG1 and IgG2a was observed compared to the control group. Furthermore, the number of parasites in the liver and spleen of vaccinated mice decreased significantly compared with the control group.